The International Minority Student Experience at the University of Birmingham Business School - Greene, Marie (2017)
The internationalisation of higher education has grown prominently in recent years. A significant manifestation of higher education internationalisation is international student recruitment, which has given prominence to the international student experience. Over the years, the number of studies concerning the international student experience has grown; however, the research remains marginal. First, research developments are dominated by international student mobility trends. Consequently, the literature is heavily focused on East Asian students. Second, research has focused on the challenges and difficulties international students face, which has in turn positioned international students as a problem group. Finally, research on the international student experience pointedly lacks perspectives from international students. This study seeks to investigate the experiences of international students who form a minority group amongst the majority of international students who come from East Asia. The study seeks to explore how international minority students construct their academic and social experiences, specifically from their perspective. This was achieved through the collection of primary research, conducted at the University of Birmingham. This research was carried out through semi-structured interviews, with eight students, which were then thematically analysed. According to this study, international minority students have a positive experience, both academically and socially. Although the students 4 portrayed a positive perception of their respective experiences, this study revealed that the students made concerted efforts to resist negative stereotypes often associated with international students. It was found that it is unhelpful to categorise all international students as having identical needs. More should be done to recognise differences, expectations, educational background and cultural contexts relating to specific nationalities, cultures and countries from students own perspectives. This approach may help to anticipate appropriate support needs and thus provide a positive experience for all international students.